A comparison of health-related quality of life in patients with periprosthetic joint infection, patients with fracture-related infections and the general population: a multicenter analysis of 384 patients from the section “Musculoskeletal Infections” of the German Society for Orthopaedics and Traumatology - Gramlich, Yves; Walter, Nike; Frese, Jasper; Steinhausen, Eva Simone; Holz, Mathias; Lazic, Igor; Morgenstern, Mario; Schaper, Björn; Gravius, Sascha; Hansberg, Jobst; Gruszka, Dominik; Clauss, Martin; et al. (Journal of Clinical Medicine, 2025)
Background: Periprosthetic joint infections (PJIs) and fracture-related infections (FRIs) are severe complications in orthopedic and trauma surgery. This study aimed to evaluate patient-reported health-related quality of life (HRQoL) in patients treated for PJI and FRI across multiple centers in Germany and Switzerland. Methods: A retrospective cohort study was conducted in nine hospitals based on a project of the Section “Musculoskeletal Infections” of the German Society of Orthopaedics and Traumatology. Patients treated in 2021 were included to ensure a minimum 12-month follow-up. Diagnoses were verified using EBJIS and FRI consensus criteria. HRQoL was assessed via telephone interviews using the EQ-5D questionnaire and a visual analog scale (VAS). Reinfection rates and additional treatments were also recorded. Generalized estimating equations (GEEs) with age and sex as covariates and clustering on center were used to compare groups, with p-values adjusted for multiple testing using the Benjamini-Hochberg false discovery rate (FDR). Results: In total, 384 patients were included (197 PJI, 187 FRI). Compared with the German reference population, both groups reported markedly reduced HRQoL across all EQ-5D domains. After adjustment, PJI patients had higher odds of reporting problems in self-care (OR 1.69, 95% CI 1.13-2.54, FDR-p = 0.033), usual activities (OR 1.68, 95% CI 1.14-2.47, FDR-p = 0.033), and pain/discomfort (OR 2.35, 95% CI 1.31-4.21, FDR-p = 0.033) compared with FRI patients. VAS scores were similar between groups (PJI: 52.8, FRI: 55.5; p = 0.489). Reinfection was associated with significantly worse outcomes: in FRI, usual activities were more impaired (OR 2.41, 95% CI 1.56-3.72, FDR-p = 0.0004); in PJI, reinfection was linked to worse mobility (OR 2.14, 95% CI 1.55-2.95, FDR-p < 0.001), self-care (OR 3.70, 95% CI 2.49-5.49, FDR-p < 0.001), and usual activities (OR 3.92, 95% CI 2.76-5.57, FDR-p < 0.001). Conclusion: This multicenter study highlights the burden of PJI and FRI on patient-reported outcomes with a significant reduction in quality of life compared to the standard population. PJI patients, in particular, experienced greater impairments in mobility, self-care, and usual activities. Reinfection was associated with poorer outcomes, underscoring the importance of patient-centered rehabilitation in managing musculoskeletal infections.
Gesehen am 08.01.2026